Conservative power theory discussion and evaluation by means of virtual instrumentation - Paredes, Helmo K. M.; Marafão, Fernando P. [UNESP]; Brandão, Danilo I. [UNESP]; Diniz, Ivando S. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2009)
Considering different single and multiphase circuits feeding linear and non-linear loads, this paper presents theoretical discussions and experimental evaluation of the recent Conservative Power Theory (CPT), by means of Virtual Instrumentation concepts. The main goal is to analyze the results of such power theory definitions under nonsinusoidal and unbalanced conditions, pointing out its major advantages, possible drawbacks or relevant aspects for discussion. © 2009 IEEE.
Keywords: Conservative power theory; Harmonic power; Power factor; Power theories; Reactive power; Virtual instrumentation; Power factors; Power theory; Virtual Instrumentation; Electric power factor; Power electronics; Instruments